(untitled) - Win, Thura (Can Tho, 2020)
An eight-week feeding trial was conduct to investigate the effects of different supplement schedules of the herbal extracts on the growth performance, innate immunity and disease resistance against Vibrio parahaemolyticus of whiteleg shrimp (Litopenaeus vannamei). Five experimental diets were prepared with supplementation of herbal extracts by 0% herbal extract, 1% Terminalia catappa extract for two week intervals and for four week intervals, 1% Sonneratia caseolaris extract for 2 week intervals, and for 4 week intervals (designated as Control, B2, B4, K2, and K4, respectively). Quadruplicate groups of shrimp (0.6 ± 0.08 g) were fed with respective diets four times a day during 8 weeks. Shrimp were sampled for determination of growth performance, immunity index (week 2, 4 and 8) and disease resistance against V. parahaemolyticus (week 4 and 8). The obtained results indicated that (i) the growth performance were significantly enhanced in whiteleg shrimp fed with 1% herbal extracts of B2, K2 and K4 treatments whereas B4 treatment was no statistically significant difference; (ii) The innate immune system parameters of herbal extracts treatments were significantly enhanced in both of supplement schedules; (iii) The cumulative mortality was difference between two week interval supplement treatments (K2-50%; B2-40%) and 4 week intervals supplement treatments (K4-30%; B4-23.3%) and lower than control treatment (63.3%).
Keywords: Nuôi tôm,Shrimp culture